3-month prevalence of unwanted sexual contact victimization in a national sample of college students: differences by race, gender identity, and sexual identity - Lisa Fedina; Anna E. Bender; Meggie Royer; Louise Ashwell; Richard Tolman; Todd I. Herrenkohl (BMC, 2024)
Abstract Importance Most unwanted sexual contact victimization (USCV) research utilizes predominantly white, cisgender, heterosexual college student samples. Estimates of USCV prevalence and demographic variation can determine the need for dedicated funding and culturally relevant campus services for students in high-risk groups. Objective To estimate the national prevalence and demographic variation in self-reported USCV within the first three months of college. Design Data are from the Sexual Assault Prevention for Undergrads (SAPU) (2020-2021) dataset. SAPU is an online intervention program administered to students on more than 600 college campuses in the United States (N = 250,359). Group differences were assessed by race/ethnicity, gender identity, and sexual identity, and then stratified by gender to assess within-gender group differences. Setting The SAPU dataset includes public and private institutions and 2-year and 4-year colleges with varying sizes of enrollment. Participants The sample is demographically diverse, and consists of newly matriculated U.S. college students, most of whom complete the SAPU program within the first three months of enrollment. Main outcomes and measures The primary outcome measure is self-reported USCV within the first three months of college enrollment, analyzed for subgroup differences. We hypothesized that USCV would be higher among students from racial/ethnic, gender, and sexual minority populations. Results Nearly 8% of transgender men reported USCV, followed by 7.4% of transgender women, 7.4% of genderqueer/gender non-conforming students, 4.5% of women, and 1.5% of men. Several subgroups reported exceedingly high rates of USCV, including Black students who identified as transgender women (35.7%) and American Indian/Alaska Native/Native Hawaiian/Pacific Islander students who identified as trans men (55.6%) or genderqueer/gender non-conforming (41.7%). Conclusions and relevance Universal and targeted (selective and indicated) intervention programs are needed to lessen USCV, particularly among gender minority students who also identify as Black, Indigenous, other person of color, or as a sexual minority.